Evaluating a custom-made agent-based driving simulator - Gregoriades, Andreas; Pampaka, Maria (My University, 2018)
We present the design and evaluation of a custom-made driving simulator, which was conducted through an experiment with users. Objective and self-reported measures of driving behaviour are used to validate the simulator. Objective data include situation awareness and workload measures, quantified with SAGAT and physiological estimates, while self-reported data focused on driving behaviour perceptions from a standardised driving style questionnaire. To evaluate the simulator, we firstly check that the synthetic environment does not overload the participants and enable them to have a sufficient level of situation awareness. Secondly, a correlation analysis is conducted between observed and self-reported driving style to examine the level of their covariance and similarity. Results showed that participants exhibited a similar driving behaviour as that reported with self-reports. This indicates that the simulator provides realistic driving conditions that encourage participants to behave in a realistic way.
Keywords: Driving behaviour; Driving conditions; Design and evaluations; Driving simulator; Situation awareness